Impact of Services Liberalization on Industry Productivity, Exports and Development : Six Empirical Studies in the Transition Countries - Tarr, David (World Bank, Washington, DC, 2012)
Services as a share of gross domestic product and in foreign direct investment flows have increased in importance both globally and in the transition countries of Europe and Central Asia. So has the need for both academics and policymakers to understand the impacts of services liberalization in the transition countries. For this reason, the World Bank Institute, under a grant from the Government of Austria, commissioned seven studies under the auspices of the Economic Education Research Consortium (headquartered in Kiev, Ukraine) to investigate the impact of services liberalization on productivity, focusing on services reform in the transition countries of Europe and Central Asia. All of the studies have been produced by authors from the transition countries of Europe or Central Asia. This paper summarizes six of these studies that will appear in a volume in Russian edited by the author of this paper. The studies contribute to the growing empirical literature establishing that liberalization of barriers against service providers can make an important contribution to increase total factor productivity, exports and growth in the economy. They also show that the issue of services liberalization is important for the transition countries in particular. Links to the English language versions of the papers are provided.